2011
DOI: 10.1155/2011/205181
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Solution of Thermal Radiation and Chemical Reaction Effects on Unsteady MHD Convection through Porous Media with Heat Source/Sink

Abstract: This paper analytically studies the thermal radiation and chemical reaction effect on unsteady MHD convection through a porous medium bounded by an infinite vertical plate. The fluid considered here is a gray, absorbing-emitting but nonscattering medium, and the Rosseland approximation is used to describe the radiative heat flux in the energy equation. The dimensionless governing equations are solved using Laplace transform technique. The resulting velocity, temperature and concentration profiles as well as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Natural convection also plays a role in stellar physics. Motivated by the investigations especially those they considered the exact analysis of the heat and mass transfer phenomenon (see for example, Seth et al [22], Toki [24], Das and Jana [26], Osman et al [27], Khan et al [28], and Sparrow and Cess [29]) and the extensive applications of non-Newtonian fluids in the industrial manufacturing sector, it is of great interest to extend the present work for non-Newtonian fluids. Of course, in non-Newtonian fluids, the fluids of second grade and Maxwell form the simplest fluid models where the present analysis can be extended.…”
Section: Future Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Natural convection also plays a role in stellar physics. Motivated by the investigations especially those they considered the exact analysis of the heat and mass transfer phenomenon (see for example, Seth et al [22], Toki [24], Das and Jana [26], Osman et al [27], Khan et al [28], and Sparrow and Cess [29]) and the extensive applications of non-Newtonian fluids in the industrial manufacturing sector, it is of great interest to extend the present work for non-Newtonian fluids. Of course, in non-Newtonian fluids, the fluids of second grade and Maxwell form the simplest fluid models where the present analysis can be extended.…”
Section: Future Recommendationsmentioning
confidence: 99%
“…They considered the impulsive, uniform, and oscillating motions of the plate with constant heat and mass diffusion and developed the exact solutions using Laplace transform technique. Recently, Osman et al [27] analyzed the thermal radiation and chemical reaction effects on unsteady MHD free convection flow through a porous plate embedded in a porous medium with heat source/sink and the closed form solutions are obtained. Khan et al [28] and Sparrow and Cess [29] analyzed the effects of Hall current and mass transfer on the unsteady MHD free convection flow in a porous channel.…”
Section: Introductionmentioning
confidence: 99%
“…Bhatti et al 23 examined the interactions of hydrodynamics metachronal waves on liquid motion through an annulus. The numerical investigation of hall current and heat transfer on peristaltic propulsion of particle-liquid suspension was calculated by Bhatti et al 24 The impact of thermal radiation and chemical reaction on magnetohydrodynamic (MHD) micropolar flow with mass and heat transfer over a moving porous plate was discussed by Mohamed and colleagues 25,26 Osman et al 27 find the solution of chemical reaction and thermal radiation influence on MHD unsteady convection flow with heat source/sink through porous media. Mohamed et al 28 scrutinized MHD unsteady double-diffusive boundary layer flow over a hot vertical plate in porous media along with heat sink and chemical reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Sharma, Chand and Chaudhary (2011) report an approximate analysis of unsteady mixed convection flow of an electrically conducting fluid past an infinite vertical porous plate embedded in porous medium under constant transversely applied magnetic field, where The transient velocity increases with increase in distance from plate until it attains its maximum value (nearly y = 1), after which it decreases. Osman et al (2011) studied thermal radiation and chemical reaction effects on the unsteady MHD convection through a porous medium bounded by an infinite vertical plate with heat source/sink. They observed that the presence of porous media increases the resistance flow resulting in a decrease in the flow velocity.…”
Section: Introductionmentioning
confidence: 99%